Mengembangkan Potensi Lokal Dalam Mewujudkan Desa Tangguh Bencana COVID 19 di Desa Patemon Kecamatan Pakem Kabupaten Bondowoso - Dwi Hastuti; Sobri Jamil; Hesti Rima Desinta (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2021)
The impact of the Covid 19 pandemic has weakened society from various aspects, including economic, social, educational and cultural aspects. So That, community empowerment efforts are needed to realize a Disaster Resilient Village against the Covid 19 pandemic. The Community Service program carries the theme of developing local potential to create a disaster resilient village in Patemon Village, Pakem District, Bondowoso Regency. The empowerment model used is the Asset Based Communities Development (ABCD) method. The program implemented includes development in the economic sector with digital marketing of ubimadu, potato crackers, gold and handicrafts (besek, furniture and sangkarayam), in education sector with teaching movement at Kindergarten Pertiwi and at Madrasah Takmiliyah Awwaliyah Hidayatullah, and making a reading garden, and in the social and healthy sector doing clean movement together on Friday, gymnastic together , share the mask to public and constructing a covid disaster resilient post. The results of the evaluation of the program get rate are very good (47%), good (40%), and enough (13%). Local potential development has helped Patemon community to advance the patemon village both from an economic, educational, social and healty. Keywords: local potential, covid-resilient village, Asset Based Communities Development (ABCD).